Pomegranate plant material: Genetic resources and breeding, a review - Mars M. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
The pomegranate (Punica granatum L., Punicaceae) is one of the oldest known fruit species. It is considered as a monoecious species developing male and perfect flowers, being self and cross-pollinated. Pomegranate grows wild in the near east, Transcaucasia and in Asia minor. Some parts of the Mediterranean area are also considered as native lands of pomegranate. Many cultivars/varieties are listed and ex situ collections are already established in different countries, but interchange of plant material is still not frequent. The description of pomegranate germplasm is based mainly on pomological and agronomic criteria and genetic studies are rare. Modern breeding objectives, systems and techniques are reviewed and discussed. Pomegranate culture is still faced with many problems. New methods must be developed for cultivar identification and improvement and genetic resources management.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)